[2.2]Paracyclophane-based N-heterocyclic carbene as efficient catalyst or as ligand for copper catalyst for asymmetric α-silylation of N-tosylaldimines. Issue 12 (5th October 2016) - Chen, Zhen; Huo, Yuwen; An, Ping; Wang, Xichao; Song, Chun; Ma, Yudao
Abstract : A carbene precursor plays a dual role as both an organocatalyst and as a ligand for the copper catalyst in asymmetric silylation. Abstract : A new series of chiral bicyclic 1, 2, 4-triazolium salts with various substituents in the pseudo- ortho position of the [2.2]paracyclophane skeleton has been successfully synthesized and applied to enantioselective α-silylations of N -tosylaldimines. The dual role of the new carbene precursor as an organocatalyst and as a ligand of the copper catalyst in the asymmetric silylation were investigated. The chiral carbene–copper catalyst has significant advantages over its carbene counterpart as an organocatalyst, affording the corresponding α-silyl amines in 77–99% yields over 20 examples and with 76–98% ee. In addition, the transannular electronic effects of the substituents in the pseudo- ortho position of the [2.2]paracyclophane skeleton were also discussed.